A Study on the Effects of Physical Properties and Thermal Properties of Nonwoven Fabric - Thirumurugan, V.; Karthikeyan, S.; Vinesh Kumar Reddy, Kota; Murugan, E. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
This paper reviews the manufacturing methods of a nonwoven with suitable fabric for thermal properties, porosity and physical properties. Nonwoven fabrics are basically classified as layers of sheet are prepared by web structures combined together by tagging fiber mechanically, thermally, chemically. The non-woven is made through needle punching, the needle punched sheets are flat and the material that are made from single separate fibers. Nonwovens are materials that are permeable and manufactured using different methods from the traditional methods of fabric manufacture. Especially while producing non-woven fabric through needle punching technique it describes more pores in its structure and using of recycled polyester helps to reduce the fabric wastage and to get the market needs. Thermal isolation is one of the important functional properties required in various field such has automobile textiles and domestic use. In this project the influence of porosity on thermal properties of polyester non-woven fabrics was analyzed.